The Use of Bimodal Subtitling in English Movie to Increase Students’ Vocabulary Mastery - Latief, Nurafni; Otoluwa, Moon H.; Badu, Helena (Transbahasa, 2023)
The aim of this research was to investigate whether the use of bimodal subtitling in English movies can increase students’ vocabulary mastery. This research used quantitative method in the form of pre-experimental research design with one group pre-test and post-test. The subjects of this research were 16 students of class X TLM 2 of SMK Teknologi Muhammadiyah Limboto in the 2022/2023 academic year. This research used purposive sampling. The technique of collecting data was used as a vocabulary test as the instrument of this research. The data was analyzed by using paired sample t-test calculations with the help of SPSS program 23 version. The outcome demonstrated a statistically significant increase in the students' mean score between the pretest and posttest with a significant level of α= 0.05. The result showed the value of Sig. (2-tailed) was 0.000 lower than < 0.05, which means H₀ was rejected and Hₐ was accepted. Therefore, it can be stated that there was an influence of the use of bimodal subtitling in English movies to increase students’ vocabulary mastery.